FORMATION AND DEVELOPMENT TRENDS OF CORPORATE GOVERNANCE OF OIL AND GAS INDUSTRY OF UZBEKISTAN FOR PROVIDING ITS SUSTAINABLE DEVELOPMENT - Karimov Mukhammad Qaxramon o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article reveals the notion of corporate governance and the approach to the problem of corporate governance from the position of the financial system. The main stages of the formation of a corporate management system in the oil and gas industry of Uzbekistan and an assessment of its effectiveness are examined. And on the basis of monitoring the development of the oil and gas industry of Uzbekistan for the years of independence, it is revealed its iterative step-by-step nature and results achieved, the structure of factors that have the greatest impact on investment attractiveness and assesses the level of investment attractiveness of oil and gas enterprises of Uzbekistan. Corporate governance systems were formed under the influence of internal and external factors and analyzed existing models of corporate governance, which showed that there are three basic models: unitary (Anglo-American), two-level (German) and network (Japanese). It shows the constituent elements of corporate governance models, the scale of corporate governance performance assessment and the system of indicators for assessing the effectiveness of corporate governance. As a result, considering the needs of the economy of the Republic of Uzbekistan, the effectiveness of corporate governance in the oil and gas industry of Uzbekistan is given to ensure the implementation of several priority areas of the industry.